Hyaline fibromatosis syndrome: a case presenting with gingival enlargement as the only clinical manifestation and a report of two new mutations in the ANTXR2 gene - Yiying Liu; Xin Zeng; Yi Ding; Yi Xu; Dingyu Duan (BMC, 2021)
Abstract Background Hyaline fibromatosis syndrome (HFS) is a rare autosomal recessive disorder caused by mutations in the gene for anthrax toxin receptor-2 (ANTXR2). The clinical features of HFS include skin thickening with nodules, papules and plaques, gingival enlargement, joint stiffness and contractures, and systemic manifestations. Notably, in all patients with HFS reported in the literature, gingival enlargement has never occurred alone. Case presentation A case of a child with gingival enlargement as the only clinical manifestation, who was later diagnosed with HFS, is described. In this case, the absence of skin and joint lesions and other characteristic clinical presentations gave rise to a diagnostic problem. This uncommon condition was clinically indistinguishable from other diseases or conditions that presented with diffuse gingival enlargement. A definitive diagnosis of HFS was reached through genetic analysis. Trio whole exome sequencing revealed compound heterozygous mutations of ANTXR2 in this patient and two new mutations were reported. Conclusions The findings of this case serve as an important reminder to clinicians. When dental practitioners encounter gingival manifestations of HFS without accompanied skin or joint involvement, there is a need to pay attention to the differential diagnosis and increase awareness of HFS.